Modelling ultrasonic sensor for gas bubble profiles characterization of chemical column - Rahiman, Mohd Hafiz Fazalul; Abdul Rahim, Ruzairi; Abdul Rahim, Herlina; Nor Ayob, Nor Muzakkir; Mohamad, Elmy Johana; Zakaria, Zulkarnay (Elsevier, 2013)
In this paper, we present a modelling and experimental work to characterize gas bubble profiles in chemical column using a pair of ultrasonic sensor. The gas bubble profiles from 2.90 mm to 7.50 mm diameter are of interest in this study. The modelling concerns ultrasonic investigation via transmission- mode technique. The modelling estimation was compared with the experimental data and the gas bubble profile characterizations from the chemical column were deduced.